(untitled) (Experimental biology, 2015)
The article presents the frequency and types of chromosomal disorders in girls (n = 50) and boys (n = 25) aged 1-18 years. Among the 33 girls diagnosed with Turner’s syndrome have a normal karyotype revealed 27 – 46, XX, the remaining 6 (18.2%) – an abnormal karyotype, of which: from 4 identified the karyotype 45,X, 1 – 46, X,i(Xq), 1 – 46,XY. In 5 girls with a diagnosis of primary amenorrhea installed a normal karyotype. Among the 12 girls with delayed puberty at 9-revealed normal karyotype – 46, XX, and at 3-altered karyotype – 45,X; 46,XX,+ mar and 46,XY. The overall incidence of abnormal karyotype in violation of sexual development in girls was 18.0%. Of 7 and boys with Klinefelter’s syndrome have a normal karyotype was observed 5 – 46, XY, at 2 revealed an abnormal karyotype – 47,ХХY and 48,XXY,+21. Among the 6-boys diagnosis of hypogonadism in 5 set normal karyotype and a 1-st – modified karyotype – 45 X / 46, XY. At the 1-st child diagnosed with cryptorchidism female karyotype revealed – 46, XX. In the 11 boys with delayed puberty karyotype was normal – 46, XY. The overall incidence of abnormal karyotype in boys with disorders of sexual development was 16.0%.